2020
DOI: 10.3390/jcm9082557
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Signs and Risk Factors in Stroke Patients

Abstract: Background: There is a pressing need to contribute evidence to the improvement in the early identification of signs and symptoms associated with strokes, and address the treatment-seeking delays. The objective of this study is to describe the knowledge regarding the warning signs and risk factors (RFs) among stroke patients, as well as of their attitudes toward a suspected event, and the analysis of its possible relationship with the socio-demographic and clinical characteristics of these patients. Method: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 62 publications
(123 reference statements)
7
34
1
5
Order By: Relevance
“…Stroke awareness in this study is also influenced by having history of stroke. In accordance with our finding, a cross-sectional study among stroke patients in Spain reported that history of prior stroke was associated with higher knowledge on stroke warning signs and risk factors [10]. Another study showed that stroke survivors or patients with history of previous stroke were more likely to have more awareness on stroke warning signs including sudden numbness or weakness, sudden difficulty speaking or understanding speech, sudden dizziness, and sudden severe headache [32].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Stroke awareness in this study is also influenced by having history of stroke. In accordance with our finding, a cross-sectional study among stroke patients in Spain reported that history of prior stroke was associated with higher knowledge on stroke warning signs and risk factors [10]. Another study showed that stroke survivors or patients with history of previous stroke were more likely to have more awareness on stroke warning signs including sudden numbness or weakness, sudden difficulty speaking or understanding speech, sudden dizziness, and sudden severe headache [32].…”
Section: Discussionsupporting
confidence: 88%
“…A recent cross-sectional study in Spain revealed that the knowledge related to the warning signs and risk factors among hospitalized stroke patients was low. Previous history of stroke and high education level were predictors which could increase the knowledge [10]. In contrast, prior study in Nigeria demonstrated different findings that the knowledge of stroke risk factors was quite high among hypertensive and diabetic patients.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…This study finding was, in contrast, to a study conducted in Spain that shows that 22.68% of the study participants identified hypertension as a stroke risk factor. 32 This inconsistency might be due to the study being conducted on admitted stroke patients, stroke may affect the intellectual ability of the study participants. Our findings were also inconsistent with studies conducted in Korea and the USA.…”
Section: Discussionmentioning
confidence: 99%
“…30 Also, our study finding was consistent with a study conducted in Spain and Ethiopia that shows having a secondary/higher level of education were the predictors of good knowledge of risk factors (OR 3.19, 95% CI 1.70–5.74; p = 0.003) and (AOR=7.128, CI 95% 2.298–22.108) respectively. 13 , 32 This similarity might be due to more literate can look up about their health from different sources. Contrasted to this study conducted in Turkey shows that there is no relationship between stroke knowledge and educational level.…”
Section: Discussionmentioning
confidence: 99%